Correlations between microstructure, fracture morphology, and fracture toughness of nanocrystalline Ni–W alloys. (1st March 2016) - Cao, Wanjun; Marvel, Chris; Yin, Denise; Zhang, Yuanyao; Cantwell, Patrick; Harmer, Martin P.; Luo, Jian; Vinci, Richard P.
Abstract: Ni-23 at.%W thin films were ion-beam machined and tested in bending. Microstructures were characterized with aberration-corrected electron microscopy and the fracture surfaces were inspected after each test with SEM. Nominally amorphous films were fractured along oxide streaks that formed during deposition. Heat treating at 700 °C crystallized the samples to a grain size of 30 nm, and the corresponding fracture toughness increased from 2.1 to 2.5 MPa m . This work demonstrates that mesoscale features and impurities influence amorphous and nanocrystalline Ni–W fracture. Graphical abstract: